Therapeutic targets for benign prostatic hyperplasia: proteome-wide Mendelian randomization and colocalization analysis - Haolin Teng; Jinyu Yu; Honglan Zhou; Faping Li (Journal of Taibah University for Science)
Background The proteomic landscape offers insights into potential therapeutic targets for benign prostatic hyperplasia (BPH). We used a Mendelian randomization (MR) approach and colocalization analysis to identify proteins and druggable targets associated with BPH risk.Methods Data from 4,907 circulating proteins in 35,559 individuals were analyzed. Single nucleotide polymorphisms associated with protein levels served as instrumental variables in a summary data-based MR analysis. Colocalization analysis was performed to identify overlapping genetic loci, and the DGIdb database was explored for therapeutic targets.Results MR analysis identified four proteins significantly associated with BPH. Specifically, BTN3A3, BTN3A1, and ASIP were found to be positively correlated with BPH, while RTP4 demonstrated a negative correlation. Colocalization analysis revealed strong support for BTN3A1 and RTP4 with BPH risk loci. The DGIdb database highlighted BTN3A3, BTN3A1, and RTP4 as potential therapeutic targets.Conclusion This study confirms the causal relationship between circulating proteins and BPH, with BTN3A1 as a promising therapeutic target.